2004
DOI: 10.1111/j.1748-5827.2004.tb00222.x
|View full text |Cite
|
Sign up to set email alerts
|

Examination of serum total IgG1 concentration in atopic and non‐atopic dogs

Abstract: In this study, serum immunoglobulin G1 (IgG1) concentrations were examined in atopic and non-atopic dogs receiving different levels of parasite control. Significantly lower serum total IgG1 concentrations were found in non-atopic dogs receiving stringent parasite control than in atopic dogs or non-atopic dogs receiving less stringent parasite control. Examination of serum total IgG1 concentrations of atopic dogs after six months of allergen specific immunotherapy (ASIT) showed a significant increase in serum t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 12 publications
(5 reference statements)
0
20
0
Order By: Relevance
“…As a result, there is an increase in allergen‐specific immunoglobulin (Ig)G, especially IgG4 and, with extended treatment, a decrease in allergen‐specific IgE. In dogs, although much less is known, a shift to a Th1 cell response, increases in IgG levels, the appearance of more Treg cells and increases in IL‐10 levels have all been demonstrated, thus establishing the parallels to ASIT in humans …”
Section: Mechanisms: the Known And The Unknownmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, there is an increase in allergen‐specific immunoglobulin (Ig)G, especially IgG4 and, with extended treatment, a decrease in allergen‐specific IgE. In dogs, although much less is known, a shift to a Th1 cell response, increases in IgG levels, the appearance of more Treg cells and increases in IL‐10 levels have all been demonstrated, thus establishing the parallels to ASIT in humans …”
Section: Mechanisms: the Known And The Unknownmentioning
confidence: 99%
“…The initial proof‐of‐concept demonstration that accelerometer based “activity monitors” could provide objective measures of pruritus in dogs has not yet been adopted in clinical trials, although advances in this technology may facilitate such in the future . Over 10 years ago, it was demonstrated that total serum IgG1 concentrations increased with successful ASIT in dogs, and the IgG response of dogs during dust mite ASIT has been studied in even more detail . The nature and functional characteristics of canine IgG subclasses have recently been described in much greater detail .…”
Section: Review Of Current Approaches To Asit In Dogs: How Well Does mentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, IgG concentrations are elevated in various allergic conditions 13–15 . Both total serum IgG 16 or allergen‐specific IgG can be raised in dogs suffering from AD, although dogs with no apparent clinical sensitivity to a particular allergen can also have elevated allergen‐specific IgG 17–19 …”
Section: Introductionmentioning
confidence: 99%
“…The initial proof-of-concept demonstration that accelerometer based "activity monitors" could provide objective measures of pruritus in dogs has not yet been adopted in clinical trials, although advances in this technology may facilitate such in the future. 33 Over 10 years ago, it was demonstrated that total serum IgG1 concentrations increased with successful ASIT in dogs, 13 and the IgG response of dogs during dust mite ASIT has been studied in even more detail. 15 The nature and functional characteristics of canine IgG subclasses have recently been described in much greater detail.…”
Section: Review Of Current Approaches To Asit In Dogs: How Well Does mentioning
confidence: 99%